Charging private electric vehicles solely by photovoltaics: A battery-free direct-current microgrid with distributed charging strategy. (1st July 2023) - Liu, Xiaochen; Fu, Zhi; Qiu, Siyuan; Zhang, Tao; Li, Shaojie; Yang, Zhi; Liu, Xiaohua; Jiang, Yi
Graphical abstract: Highlights: Battery-free DC microgrid is proposed to charge private EVs solely by PV. It provides intermittent but free charging service to cover intra-urban transportation. Influence of intermittent charging on service quality is quantified. Distributed charging strategy takes the role of energy storage for PV-EV synergy. Building-connected microgrid can improve SCR and avoid distribution grid upgrade. Abstract: Charging electric vehicles (EV) by photovoltaics (PV) contributes to achieving carbon neutrality, but puts pressure on urban renewal, e.g., large investments in distribution grid upgrade and energy storage (ES). To solve this problem, we proposed a charging system aiming at providing intermittent but free solar charging service for private EV drivers to cover their daily intra-urban transportation demand. It is a battery-free direct-current (DC) microgrid with a distributed charging strategy, taking variable DC bus voltage as a control signal. The system was optimized and tested by simulation on an office building with 80 private EVs. We performed a system performance comparison, when achieving the same guarantee level of EV use with the parking shed fully cover by PV. A 10-kW charger (DC Level 1) with the strategy can take the role of a 3.5-kW charger (AC Level 2) with ES (26.0 kWh/parking space) to coordinate PV generation and charging load. Furthermore, connecting the system with the adjacent building can increase the annual solar self-consumption rate from 33.3% to 67.9%, and avoid the distribution grid upgrade (average 5.6 kVA/charger). The discounted payback time of this building-connected system decreases from 9.4 to 4.5 years, compared with a conventional solar charging station.